2018
DOI: 10.2478/jeb-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Variations in Consumer Behavior: A Literature Review of International Studies

Abstract: The timeliness of studying the behavior of consumers from different cultures in an increasingly fragmented world is demonstrated by the dynamic growth of the number of published cross-cultural studies and the rise of special issues of consumer behavior-related journals. Researchers challenging consumer behavior variations from a cross-cultural standpoint encounter substantial challenges, including issues that arise from the diversity of domains and interdisciplinary approaches, such as the variety of methods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Concerning the different strategies used to carry out inferential analysis and multivariate analysis in cross-cultural studies, it should be noted that the study by Sin et al (1999) established analysis of variance and factor analysis as the most common for this type of study. Afterward, in Galina et al (2018), although there is a greater variety of statistical techniques applied to the area of knowledge, these techniques continue to be the most widely used to observe differences and similarities in the countries under analysis. Based on the above, the following analyses were carried out to answer the research questions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerning the different strategies used to carry out inferential analysis and multivariate analysis in cross-cultural studies, it should be noted that the study by Sin et al (1999) established analysis of variance and factor analysis as the most common for this type of study. Afterward, in Galina et al (2018), although there is a greater variety of statistical techniques applied to the area of knowledge, these techniques continue to be the most widely used to observe differences and similarities in the countries under analysis. Based on the above, the following analyses were carried out to answer the research questions.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the comparability of samples, although participants’ inclusion criteria were applied as rigorously as possible in the three countries to obtain homogeneous samples, a significant aspect in this type of study is that results must be interpreted considering their exploratory and descriptive scope. Furthermore, although the techniques suggested in the literature were used to conduct cross-cultural studies, conceptual frameworks and criteria for identifying cross-cultural variations still need to be developed further in the absence of a unified terminology for this type of research (Galina et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of the Internet has provided global marketers with more opportunities to interact with customers online, and cross-cultural marketing research has received extensive attention from scholars. Studies have suggested that global culture has a significant influence on customer behavior(Cruz-C ardenas et al, 2019;Galina et al, …”
mentioning
confidence: 99%